1996
DOI: 10.1128/jb.178.20.5938-5945.1996
|View full text |Cite
|
Sign up to set email alerts
|

Purification and cloning of a thermostable xylose (glucose) isomerase with an acidic pH optimum from Thermoanaerobacterium strain JW/SL-YS 489

Abstract: An unusual xylose isomerase produced by Thermoanaerobacterium strain JW/SL-YS 489 was purified 28-fold to gel electrophoretic homogeneity, and the biochemical properties were determined. Its pH optimum distinguishes this enzyme from all other previously described xylose isomerases. The purified enzyme had maximal activity at pH 6.4 (60؇C) or pH 6.8 (80؇C) in a 30-min assay, an isoelectric point at 4.7, and an estimated native molecular mass of 200 kDa, with four identical subunits of 50 kDa. Like other xylose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 49 publications
2
38
0
Order By: Relevance
“…However, such enzymes are still required to perform catalytic activity under conditions for which they have not evolved. For instance, catalysis at such high temperatures and neutral pHs causes browning and other unwanted side reactions (18,29). Ideally, industry requires AIs that are able to perform a highly efficient enzymatic process with high yield at moderately high temperatures and slightly low pHs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such enzymes are still required to perform catalytic activity under conditions for which they have not evolved. For instance, catalysis at such high temperatures and neutral pHs causes browning and other unwanted side reactions (18,29). Ideally, industry requires AIs that are able to perform a highly efficient enzymatic process with high yield at moderately high temperatures and slightly low pHs.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, isomerization performed at higher temperatures (Ͼ70°C) offers several advantages, such as higher conversion yield, faster reaction rate, and decreased viscosity of the substrate in the product stream. However, higher-temperature processes introduce undesired effects like browning and unwanted by-product formation (29). In order to overcome these problems, a thermostable AI with an acidic pH optimum (pH opt ) would be desirable and crucial for industrial applications.…”
mentioning
confidence: 99%
“…A number of thermostable xylose isomerases (XIs) (EC 5.3.1.5) have been isolated from extremophiles and have been studied extensively in connection with the manufacture of high-fructose corn syrup, because the equilibrium for the isomerization of glucose to fructose is shifted toward fructose at high temperatures (17,27,29).…”
Section: ؊1mentioning
confidence: 99%
“…It has also been classified as generally recognized as safe for use in cosmetics and drugs, and it is useful as a reduced-calorie bulking agent, as an intermediate in the synthesis of other optically active compounds, and as an additive in detergent, cosmetic, and pharmaceutical formulations. Initial quantities of D-tagatose have been produced commercially by a patented chemical process since the beginning of 2003 (2).A number of thermostable xylose isomerases (XIs) (EC 5.3.1.5) have been isolated from extremophiles and have been studied extensively in connection with the manufacture of high-fructose corn syrup, because the equilibrium for the isomerization of glucose to fructose is shifted toward fructose at high temperatures (17,27,29).Our preliminary experiments on the effect of reaction temperature on the conversion of D-galactose to D-tagatose by Thermotoga neapolitana AI showed that conversion increased as the incubation temperature was raised (12). For industrial applications of the production of D-tagatose from D-galactose, the AI should be thermostable at elevated temperatures (Ͼ50°C).…”
mentioning
confidence: 99%
“…Species of Thermoanaerobacterium are widely distributed and can efficiently utilize xylan, a potentially inexpensive substrate for industrial fermentation (15). Several enzymes from Thermoanaerobacterium saccharolyticum strain JW/SL-YS485 have been isolated and characterized, and various genes have been cloned and sequenced (10,(12)(13)(14). Due to lack of developed genetic systems for any member belonging to this group of microorganisms, T. saccharolyticum JW/SL-YS485 was chosen as a model organism for the development of genetic tools (16).…”
mentioning
confidence: 99%